2012
DOI: 10.1371/journal.pone.0048844
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Fluctuating Asymmetry and Shape Variation in Chironomus riparius (Diptera, Chironomidae) Exposed to Nonylphenol or Lead

Abstract: Deformities and fluctuating asymmetry in chironomid larvae have been proposed as sensitive indicators of biological stress and are commonly used to assess the ecological impact of human activities. In particular, they have been associated in Chironomus riparius, the most commonly used species, with heavy metal and pesticide river pollution. In this study, the effect of lead and 4-nonylphenol on mouthpart morphological variation of Chironomus riparius larvae was investigated by traditional and geometric morphom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 68 publications
1
27
0
Order By: Relevance
“…This result agrees with those of Bird et al , who did not notice any size variations in Chironomus tentans larvae exposed for 2 wk to Pb sediment concentrations lower than 5000 mg/kg dry weight. Moreover, according to previous studies in Chironomus larvae exposed to Pb‐spiked sediment , no significant increase in the frequency of mouthpart deformities was observed. This result suggests that the energy consumption observed in the present study was insufficient to induce growth retardation and mentum morphological defects.…”
Section: Discussionsupporting
confidence: 59%
“…This result agrees with those of Bird et al , who did not notice any size variations in Chironomus tentans larvae exposed for 2 wk to Pb sediment concentrations lower than 5000 mg/kg dry weight. Moreover, according to previous studies in Chironomus larvae exposed to Pb‐spiked sediment , no significant increase in the frequency of mouthpart deformities was observed. This result suggests that the energy consumption observed in the present study was insufficient to induce growth retardation and mentum morphological defects.…”
Section: Discussionsupporting
confidence: 59%
“…Further non-significant results were reported from mites [128] and wings of Trichogramma egg parasitoids [129]-but both studies reported results only from relatively small subsamples (≤30 specimens per sample) and tiny organisms, raising questions about statistical power and possible artifacts from mounting very small specimens. Further negative results come from two datasets of wings from Chironomus midges [116], whereas other studies found mixed results for wings and larval mouthparts [103,130,131]. Some studies, in a variety of species, have found mixed results, with some structures or subgroups yielding significant results, but others not [132][133][134][135][136][137][138].…”
Section: Directional Asymmetrymentioning
confidence: 99%
“…Several studies found greater fluctuating asymmetry in disturbed than in undisturbed habitats for skull shape of voles [250], in areas of worse rather than better climatic suitability for skull shape of Akodon rodents [370], in urban than in rural habitats for head shape of lizards [106], in polluted than unpolluted habitats for crab carapace shape [253] and for mandible shape of shrews [371]. Studies of the larval mentum and adult wings in chironomid midges showed that pollution in the rearing environment had no or only limited effects on fluctuating asymmetry [130,131] or that there was more fluctuating asymmetry in offspring reared in unpolluted sediment in the laboratory than in the parental generation collected from polluted sediment in the field [103]. Temperature stress had no significant effect on fluctuating asymmetry of body shape in bulb mites [372], but fluctuating asymmetry of shape has been shown to be influenced by temperature in aphid [164] and Drosophila wings [62,121].…”
Section: Developmental Instability Of Shape In Relation To Stress Andmentioning
confidence: 99%
“…Permutation ANOVA tests were then used to compare FA CS according to age group and sex. Finally, to address the question of size scaling and check whether FA in centroid size increases with size, non‐parametric Spearman correlation tests were performed in each sample between individual FA CS scores and mean size ( R + L )/2 (Arambourou, Beisel, Branchu, & Debat, ; Graham and Ozener, ; Graham, Raz, Hel‐Or, & Nevo, ; Palmer, ).…”
Section: Methodsmentioning
confidence: 99%